Towards patient-specific articulating implants: wear properties of polymeric materials on additively manufactured metallic alloys - Cremer, Labau (Stellenbosch : Stellenbosch University, 2025)
Cremer, L. 2025. Towards patient-specific articulating implants: Wear properties of polymeric materials on additively manufactured metallic alloys. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/29da81c3-79a0-419b-a4ab-b8256e4bfd81